A survey of farm credit in Kenya - Donaldson, G.F.; Von Pischke, J.D.; Agency for International development (Washington DC Agency for International Development, 1973)
Reviews credit provision and requirements in the farm sector and discusses the related policy issues and strategies.
aia 26/02/2019
Loans
Keywords: Economic Aspect; Kenya